Cultivation of fig (Ficus carica), Loquat (Eriobotrya japonica), Japanese persimmon (Diospyros kaki), Pomegranate (Punica granatum) and Barbary fig (Opuntia ficus-indica) in Cyprus - Gregoriou C. (Underutilized fruit crops in the Mediterranean region, 1995)
Pomegranate (Punica granatum), fig (Ficus carica), and loquat (Eriobotrya japonica) culture in Cyprus is very ancient and there are commercial plantations based mainly on local varieties. The bulk of production of these crops is for local consumption and the prices obtained are reasonable. On the other hand, the production of persimmon (Diospyros kaki) which was introduced later is limited but shows an increasing trend. The Barbary fig (Opuntia ficus-indica) still remains to be a wild species.
First meeting of the CIHEAM Cooperative Working Group on Underutilized Fruit Crops in the Mediterranean Region, 1994/11/09-10, Zaragoza (Spain)